2011
DOI: 10.1107/s0907444911032835
|View full text |Cite
|
Sign up to set email alerts
|

Can radiation damage to protein crystals be reduced using small-molecule compounds?

Abstract: Recent studies have defined a data-collection protocol and a metric that provide a robust measure of global radiation damage to protein crystals. Using this protocol and metric, 19 small-molecule compounds (introduced either by cocrystallization or soaking) were evaluated for their ability to protect lysozyme crystals from radiation damage. The compounds were selected based upon their ability to interact with radiolytic products (e.g. hydrated electrons, hydrogen, hydroxyl and perhydroxyl radicals) and/or thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 81 publications
4
53
3
Order By: Relevance
“…The B-factor-derived dose estimates given above should thus be considered accurate to within 50%. However, unlike in our quantitative studies of global radiation damage (Kmetko et al, 2006(Kmetko et al, , 2011Warkentin & Thorne, 2010;Warkentin et al, 2011Warkentin et al, , 2012, none of the present conclusions rely on the precise global damage or dose estimates and are robust against sample-to-sample variability of global sensitivity.…”
Section: Sample Mounting and Data Collectioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The B-factor-derived dose estimates given above should thus be considered accurate to within 50%. However, unlike in our quantitative studies of global radiation damage (Kmetko et al, 2006(Kmetko et al, , 2011Warkentin & Thorne, 2010;Warkentin et al, 2011Warkentin et al, , 2012, none of the present conclusions rely on the precise global damage or dose estimates and are robust against sample-to-sample variability of global sensitivity.…”
Section: Sample Mounting and Data Collectioncontrasting
confidence: 60%
“…Protein crystals are approximately 10-130 times more sensitive to global damage at room temperature than at cryogenic temperatures ($100 K; Blake & Phillips, 1962;Teng & Moffat, 2002;Kmetko et al, 2006Kmetko et al, , 2011Southworth-Davies et al, 2007;Barker et al, 2009;Warkentin & Thorne, 2010). Solvent and atomic radical diffusion and diffusive motions of protein side chains and larger structural elements are suppressed below the proteinsolvent glass-transition temperature near T ' 200 K and become negligible by $100 K (Rodgers, 1994;Garman & Schneider, 1997;Weik, Kryger et al, 2001;Garman, 2003;Weik et al, 2004Weik et al, , 2005Warkentin & Thorne, 2009, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, the advantages of including such compounds are unclear. There are several studies which report conflicting evidence of their efficacy at mitigating radiation damage [30][31][32][33], and only one study has proved it beneficial during room-temperature data collection [34]. In the worst-case scenario, inclusion of metal containing scavengers and crystallisation reagents will merely add to the heavy atom content of the crystal and increase its X-ray absorption, making it more sensitive to radiation damage.…”
Section: Crystallisationmentioning
confidence: 99%
“…Still, a study of lysozyme crystals showed that none of the 19 different added molecules caused a decrease in global protein damage at 100 K while many acted as sensitizers at room temperature. This was attributed to having the additives present some distance from the site of primary X‐ray absorption by the protein . Hence, as detailed below, the main outcome of the absorbed radiation is production of mobile species such as reducing and oxidizing radicals.…”
Section: Radiation Induced Damagementioning
confidence: 99%